Catalogue manager for metadata dissemination in the NetTraveler middleware system. (16th May 2011) - Moreno-Puello, Oliver; Rodriguez-Martinez, Manuel
Distributed databases hold the promise of interconnecting mobile devices, workstations, and servers to share data and computational resources. In these environments, query optimisers will be as good as the metadata they use in the optimisation process. The dynamic nature of mobile and wide-area networks results in constant changes to the metadata and to the sites holding such metadata. Hence, it is of paramount importance to have a catalogue system that dynamically adapts to these changes. This work presents a decentralised framework for metadata management that copes with this situation. Our approach is based on a peer-to-peer catalogue management organisation, using consistent hashing as the mechanism to locate metadata objects. Our framework makes the system more scalable since there is no central metadata repository and metadata can be found through an efficient search mechanism. It also provides efficient mechanisms to handle the arrival and departure of hosts in the system.